Glomeruloesclerose segmentar e focal primária [manuscrito]; curso clínicoe fatores preditores da resposta ao tratamento em crianças e adolescentes - Roberta Gazzi Salum (2008)
Introduction: Focal and segmental glomerulosclerosis (FSGS) is the main cause of steroidresistant nephrotic syndrome in children and also one of the most common causes of chronic renal disease. The objective of this study was to describe the response to treatment in childrenwith FSGS and to correlate it with the clinical, laboratory and pathologic classification parameters. Method: retrospective study of 113 children and adolescents between 1 and 18 years of age with a primary diagnosis of FSGS, confirmed by means of renal biopsy, admitted to the Unit of Pediatric Nephrology at the HC-UFMG between 1970 and 2007. Results: all patients were initially treated with oral prednisone: 42 (37.2%) achieved complete remission and 25 (22.1%) showed partial response. The presence of hematuria (p=0,001) and older children at the beginning of the symptoms (p=0,034) were associated with poor response toprednisone. Eighty four patients (74.3%) were given cyclophosphamide (CPM). Forty-two (50%) achieved complete remission where as response was partial for 16 (19%). Complete remission or partial response to the initial course of prednisone. was associated with the response to CPM Those with nonresponse to initial steroid treatment had 3.8 times more risk of nonresponse to CPM, while the later nonresponse to steroid treatment had 15.7 times more probability of nonresponse to CPM. CsA was administered to 27 patients of which 22 (81.5%) achieved remission after the use of the CsA: all steroid-sensitive and 12 (71%) of the steroidresistant. Only the level of proteinúria in 24-hour urine at the time of admission was a risk factor associated with nonresponse to CsA in multivariate analysis. Renal survival was better in the group of steroid-sensitive patients (p=0,0002). The response to the CPM, even partial, as well as the response to the CsA, was related to better preservation of renal function. Conclusion: the presence of hematúria at the time of admission and older children at the beginning of the symptoms (p=0,034) were related to steroid nonresponse. Steroids sensitivity was associated with better response to CPM and CsA treatment. Higher proteinuria at admission was associated with nonresponse to CsA. None of the histological features of FSGS weresignificant predictors of the response to treatment. The nonresponse to treatment was associated with chronic kidney failure. Patients with complete or partial response to prednisone, CPM or CsA had an improved clinical course. The nonresponse to treatment was a risk factor associated with chronic kidney failure.